Model evaluation of solar radiation on an inclined plane - GARG, H. P.; GARG, SAT NARAIN (MAUSAM, 1982)
In this paper an attempt has been made to evaluate some of the different methods available for estimating global solar radiation on an inclined plane, from the solar energy utilization point of view. Three commonly used methods like the Beam method, Liu and Jordan’s method (using daily values and hourly values), and the Klucher method are discussed. It is observed that while the beam method overestimates the radiation, Liu & Jordan’s both methods, always underestimate it. The Klucher method gives the least error under all weather conditions and is hence recommended for use in tropical countries.